Tanggung Jawab Dinas Perdagangan Kota Kupang Terhadap Pengawasan Dan Penertiban Penjualan Pakaian Bekas Ditinjau Dari Peraturan Menteri Perdagangan Nomor 40 Tahun 2022 Tentang Larangan Impor Pakaian Bekas - Yohanes Alexandro Paso; Yosef Mario Monteiro; Cyrilius W.T. Lamataro (Pemuliaan Keadilan, 2024)
This study aims to determine the responsibility of the Kupang City Trade Office for the supervision and control of the sale of used clothes in Kupang City as well as the inhibiting factors for the implementation of the responsibility of the Kupang City Trade Office for the supervision and control of the sale of used clothes in Kupang City. To answer the above problems, this research method uses the Empirical Law research method using primary data and secondary data. The results of the discussion in this study show that, (1) The implementation of the responsibility of the Kupang City Trade Office for the supervision and control of the sale of used clothes The Kupang City Trade Office has never formed a single derivative policy/regulation as a follow-up to the regulation of the Minister of Trade No. 40 of 2022 on the ban on the import of used clothes, coordination between the Trade Office and SATPOL PP which is carried out in measuring the extent of the stages of Supervision and The control of the sale of used clothes has not been effective, the socialization carried out by the Kupang City Trade Office does not cover the possibility that the Kupang City Trade Office still finds business actors who sell used clothes. (2) Factors that hinder the implementation of the responsibility of the Kupang City Trade Office for the supervision and control of the sale of used clothes in Kupang City, namely Human resources owned by Trade Office employees are still not good, The low awareness of traders and consumers towards the applicable law makes business actors continue to sell used clothes even though there are regulations on the prohibition of selling used clothes, Inadequate infrastructure greatly affects the responsibility of the Trade Office in supervising and controlling imported used clothes in Kupang City as well as the culture of shopping for imported clothes, this culture is very popular among people to wear used clothes.